The Doctrine of Salvation in the First Letter of Peter - Williams, Martin (Martin Patrick) (Cambridge : Cambridge University Press, 2011)
Provides an invaluable theological discussion of the concept of salvation in the first letter of Peter.
Future salvation as hope and inheritance (1:3-5).
Print version record.
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible; Salvation -- Biblical teaching; Religion; RELIGION -- Biblical Studies -- New Testament; Salvation -- Biblical teaching; Electronic books; Criticism, interpretation, etc